2001
DOI: 10.1002/ajh.1122
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of cervical lymph nodes by B‐ and T‐cell non‐Hodgkin's lymphoma and Hodgkin's lymphoma: Preliminary ultrasonic findings

Abstract: Ultrasonography has been used in the evaluation of enlarged lymph nodes in patients with malignant lymphoma, which comprises a variety of histopathological subtypes. We assessed ultrasonic findings of infiltration in cervical lymph nodes of 47 patients with previously untreated malignant lymphoma and correlated them with histopathological subtypes. Common findings among various histopathological subtypes were hypoechoic masses, spot and/or line echoes, involvement of multiple nodes, and posterior enhancement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…It is very much comparable to other studies, Stark GL observed 36% in early stage, 64% in advance diseases while Hong et al, analyzed 34 patient of Hodgkin's lymphoma in Taiwan in 1992, revealing extremely high incidence (80.6%) of advance clinical stage (III and IV) 12,13 . In our study mixed cellularity was most common (45%) where as in other studies nodular sclerosis was more common (44-69%) 3,12,14 .…”
Section: Resultssupporting
confidence: 66%
“…It is very much comparable to other studies, Stark GL observed 36% in early stage, 64% in advance diseases while Hong et al, analyzed 34 patient of Hodgkin's lymphoma in Taiwan in 1992, revealing extremely high incidence (80.6%) of advance clinical stage (III and IV) 12,13 . In our study mixed cellularity was most common (45%) where as in other studies nodular sclerosis was more common (44-69%) 3,12,14 .…”
Section: Resultssupporting
confidence: 66%
“…Sonography is used to evaluate various diseases of superficial organs of the craniocervical region, such as the submandibular glands and organs involving regional lymphadenopathy 4 8 . This modality is noninvasive, inexpensive, and efficient in assessing these diseases as the initial examination of choice.…”
mentioning
confidence: 99%
“…Sonography has been used for evaluation of diseases of the submandibular glands and regional lymphadenopathy 13 17 . It is a noninvasive, inexpensive, and efficient examination to evaluate these diseases as an initial investigation of choice.…”
mentioning
confidence: 99%